2001
DOI: 10.1007/s001250051601
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycaemia in vitro alters the proliferation and mitochondrial activity of the choriocarcinoma cell lines BeWo, JAR and JEG-3 as models for human first-trimester trophoblast

Abstract: Despite considerable advances in the treatment of diabetes in the past decades, diabetic pregnancies can still be associated with fetal growth disturbances even when an optimized and intensive metabolic control has been achieved. Macrosomia of the fetus is a common and well-known consequence of maternal diabetes with an increased obstetric risk. The increase in fetal fat mass that accounts for the fetal overweight [1] is the result of fetal hyperinsulinism as a consequence of maternal and, therefore, fetal hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 33 publications
4
63
1
2
Order By: Relevance
“…We speculate that high glucose levels in early pregnancy may harm placental development and thus the capacity for fetal growth, such that the effect of hyperglycaemia in later pregnancy is permanently attenuated. The presence of microvascular disease, in particular in combination with first-trimester hyperglycaemia, can inhibit trophoblast proliferation, thereby reducing placental growth and impairing uteroplacental function, which may result in subsequent intrauterine growth restriction [10,37]. In our study, microvascular complications (pre-pregnancy retinopathy and/or nephropathy) in women with diabetes were associated with lower birthweight.…”
Section: Discussionmentioning
confidence: 53%
“…We speculate that high glucose levels in early pregnancy may harm placental development and thus the capacity for fetal growth, such that the effect of hyperglycaemia in later pregnancy is permanently attenuated. The presence of microvascular disease, in particular in combination with first-trimester hyperglycaemia, can inhibit trophoblast proliferation, thereby reducing placental growth and impairing uteroplacental function, which may result in subsequent intrauterine growth restriction [10,37]. In our study, microvascular complications (pre-pregnancy retinopathy and/or nephropathy) in women with diabetes were associated with lower birthweight.…”
Section: Discussionmentioning
confidence: 53%
“…This method has been recently used to demonstrate the effects of hyperglycaemia on choriocarcinoma cells (Weiss et al 2001).…”
Section: Determination Of Cell Numbermentioning
confidence: 99%
“…Proteins (40 mg) of adherent cells were subjected to SDS-PAGE and immunoblotting as described (Weiss et al 2001). The blotting membranes were incubated (overnight, 4 8C) with either a polyclonal anti-GC receptor antibody (1:500; P-20 Santa Cruz; Santa Cruz, CA) or a monoclonal anti-cyclin B1 antibody (1:500; Pharmingen, San Diego, CA).…”
Section: Immunoblotting Of Gc Receptor and Cyclin B1 Proteinmentioning
confidence: 99%
“…These cells maintain in culture many features characteristic of human first trimester trophoblast, including chorionic gonadotropin and progesterone secretion (21). Because of these features, JAr cells have been widely used to investigate glucose and insulin action in placenta (19,20). We found that insulin does not induce proliferation of JAr cells when they are maintained in low glucose medium.…”
Section: Resultsmentioning
confidence: 84%